CFD study on mechanisms of fission gas burst release from defective fuel rods of a typical PWR. (1st June 2020) - Dong, Bing; Li, Chenyue; Li, Leihao; Yin, Junlian; Wang, Dezhong
Highlights: Fission gas burst release mechanisms under PWR fuel defective conditions are revealed. The short-term fission gas release process has been simulated using the VOF method. Sensitivity analysis of short-term release has been performed to find the critical factor. Steam generation rate in the gap is the most relevant parameter for the short-term fission gas release rate. Abstract: During the reactor operation, it is necessary to estimate the amount of fission gas release from the fuel-cladding gap to the coolant. The most common method for predicting the fission gas release process is based on the first-order kinetic model, which is used for analysis of the steady-state stage of the fission gas release. The purpose of this paper is to reveal the fission gas burst release mechanisms under PWR fuel defective conditions. The fission gas release process has been simulated using the CFD method. A validation calculation has been performed to validate the method. The simulation results are discussed in the paper including the two-phase flow evolution and the amount of fission gas release over time. For short stage after the equilibrium, the gas phase is released in the coolant by the form of jet. While for long stage after the equilibrium, the gas phase is entrained into the coolant by the vortex in the defect site. Sensitivity analysis of short-term fission gas release has been performed to evaluate which parameter critically influenced the release process. The results show that steam generation rate in the gap is the most relevant parameter for the short-term fission gas release rate.